Rab10-Positive Tubular Structures Represent a Novel Endocytic Pathway That Diverges From Canonical Macropinocytosis in RAW264 Macrophages - Kawai, Katsuhisa; Nishigaki, Arata; Moriya, Seiji; Egami, Youhei; Araki, Nobukazu (Frontiers in Immunology, 2021)
Using the optogenetic photo-manipulation of photoactivatable (PA)-Rac1, remarkable cell surface ruffling and the formation of a macropinocytic cup (premacropinosome) could be induced in the region of RAW264 macrophages irradiated with blue light due to the activation of PA-Rac1. However, the completion of macropinosome formation did not occur until Rac1 was deactivated by the removal of the light stimulus. Following PA-Rac1 deactivation, some premacropinosomes closed into intracellular macropinosomes, whereas many others transformed into long Rab10-positive tubules without forming typical macropinosomes. These Rab10-positive tubules moved centripetally towards the perinuclear Golgi region along microtubules. Surprisingly, these Rab10-positive tubules did not contain any endosome/lysosome compartment markers, such as Rab5, Rab7, or LAMP1, suggesting that the Rab10-positive tubules were not part of the degradation pathway for lysosomes. These Rab10-positive tubules were distinct from recycling endosomal compartments, which are labeled with Rab4, Rab11, or SNX1. These findings suggested that these Rab10-positive tubules may be a part of non-degradative endocytic pathway that has never been known. The formation of Rab10-positive tubules from premacropinosomes was also observed in control and phorbol myristate acetate (PMA)-stimulated macrophages, although their frequencies were low. Interestingly, the formation of Rab10-positive premacropinosomes and tubules was not inhibited by phosphoinositide 3-kinase (PI3K) inhibitors, while the classical macropinosome formation requires PI3K activity. Thus, this study provides evidence to support the existence of Rab10-positive tubules as a novel endocytic pathway that diverges from canonical macropinocytosis.